Temperature dependent electronic conduction through graphene oxide thin film based two terminal devices. Issue 184 (13th October 2017) - Saini, Pooja; Jain, Harsh; Tandon, Ram P.; Singh, Surinder P.; Mahapatro, Ajit K.
ABSTRACT: The temperature dependent electronic conduction through GO thin films sandwitched between indium tin oxide (ITO) substrates and top thermally deposited Al electrode (Al/GO/ITO) is explained. The curent-voltage (I-V) characteristic are measured at various temperatures range of 10–100°C. The temperature dependent I-V through Al/GO/ITO structures in both the forward (ITO as anode) and reverse (ITO as cathode) directions, demonstrate Ohmic behavior with an estimated value of temperature coefficient of resistance 4.2 × 10 −3 identical to the value for Al. The electrical current decreases with increasing temperature at an applied voltage, suggesting the metallic behaviour arising from the formation of Al filament through the GO films.